QUINTERO, Inés; ALMARZA, Ángel; BIFANO, José; MUÑOZ, Lionel; RAMÍREZ, Enrique; VARGAS, Rosangel; VERGARA, Johana y ZAMBRANO, Alexander: Más allá de la Guerra. Venezuela en Tiempos de la Independencia. Caracas: Fundación Bigott, 2008 (Bigotteca, Serie Hist - Niño Sánchez, Gladys Teresa (Studia Historica. Historia Contemporánea, 2011)
Reseña